Pengembangan Lembar Kegiatan Peserta Didik (LKPD) Materi Praktikum Akuntansi Dagang Berbasis Higher Order Thinking Skills (HOTS) - Sulistiowati, Ayu Pawistri; Susilowibowo, Joni (JPAK : Jurnal Pendidikan Akuntansi dan Keuangan, 2021)
Education in Indonesia, there is a development of a curriculum called â€œCurriculum 2013 Revised 2018â€. The curriculum is integrated with 21st century learning. From the implementation of the â€œCurriculum 2013 Revised 2018â€, Indonesian government pioneered HOTS-based learning programs (Ditjen GTK, 2018). HOTS learning is applied in teaching materials in the form of Student Activity Sheets (LKPD). LKPD which was developed on the subject of the Trade Accounting Practicum, is expected to be able to achieve the learning objectives by applying the HOTS program which is contained in questions in the form of company transaction documents so that they are not narrative-based. LKPD is prepared with case studies of three different company criteria and an integrated presentation of cases in the form of a company's financial cycle. The purpose of this study was to determine the feasibility of the LKPD developed as teaching materials. In this study using the 4D-Thiagarajan research model which includes the stages: Define, Design, Develop and Dessiminate. However, it is limited to the Develop stage. The research method uses qualitative methods and quantitative methods. The data collection instrument used two types of questionnaires, namely open questionnaires and closed questionnaires. In the data analysis from the results of the feasibility study of the developed LKPD, the results of product validation were obtained with an average rating of "Very Appropriate" from the assessment of material feasibility, language feasibility and graphic feasibility.